Evaluation of Owner Estimated Reviews Effectiveness by Inspektorat Kabupaten Jombang to Reduce Corruption Potential (Case Study on 10 Regional Strategic Projects of Kabupaten Jombang In 2023 Financial Year): Evaluasi Efektivitas Reviu Harga Perkiraan Sendiri oleh Inspektorat Kabupaten Jombang Guna Mengurangi Potensi Korupsi (Studi Kasus 10 Proyek Strategis Daerah Kabupaten Jombang Tahun Anggaran 2023) - Elsa Khoirun Nisa; Maulidya Octaviani B; Wisnu Abiarto N (Universitas Negeri Surabaya, 2025)
Owner Estimated Reviews are conducted to provide limited assurance that Owner Estimated was prepared by Pejabat Pembuat Komitmen with correct procedures, reasonable price, accounted with applicable regulations, no additional price, and no unnecessary cost items. To ensure the review can be achieved, work steps are used to guide for review review assignment. The method that used in this research is comparative analysis of the results of the Owner Estimated Reviews are conducted by Inspektorat with the Audit Reports are conducted by Badan Pemeriksa Keuangan. The review work steps are also used as a media for make review result conclusions through review procedures that have been carried out systematically. Owner Estimated Reviews that conducted by Inspektorat Kabupaten Jombang has analyzed the use of unit prices, the relevance between work items and work objects, and the use of the Analisa Harga Satuan Pekerjaan (AHSP) that used in making Owner Estimated. It has been optimal in the use of the finance because even though there is efficiency, but the work can be conducted well by contractor. And it has effectiveness to reduce corruption potential based on case study 10 Regional Strategic Projects of Kabupaten Jombang In 2023 Financial Year with percentage of 90%.